Bahaja Menghantjam: Ups And Downs of the New PNI Movement 1931-1942 - Ilham Nur Utomo; Agustinus Supriyono; Indriyanto Indriyanto (IHiS (Indonesian Historical Studies), 2021)
The non-cooperative nationalist organization movement in the 1930s came under pressure from the colonial government through the enactment of vergader verbod so that most of the non-cooperative nationalist organizations dissolved and their former cadres joined the cooperative organization movement. The New PNI as a non-cooperative nationalist organization was still able to survive in the midst of a repressive government and economic depression that hit the Dutch East Indies economy. The discussion in this article focuses on the ups and downs of the New PNI movement in 1931-1942. The method used in this research was the historical method consisting of heuristics, source criticism, interpretation, and historiography. The findings indicated that the New PNI was still able to survive in the dynamics of the Indonesian independence movement even though it had to experience downturn from August 1933 to 1942 as an implication of vergader verbod. The factors that allowed the New PNI to survive were changing the movement pattern to an underground movement and rearranging the organizational structure when the New PNI leaders were arrested by PID. The survival of the New PNI in the dynamics of the independence movement proved the success of cadre education carried out by the New PNI.